Regulator of G-Protein Signaling 10 Negatively Regulates Cardiac Remodeling by Blocking Mitogen-Activated Protein Kinase–Extracellular Signal-Regulated Protein Kinase 1/2 Signaling. Issue 1 (January 2016) - Miao, Rujia; Lu, Yao; Xing, Xiaowei; Li, Ying; Huang, Zhijun; Zhong, Hua; Huang, Yun; Chen, Alex F.; Tang, Xiaohong; Li, Hongliang; Cai, Jingjing; Yuan, Hong
Abstract : Regulator of G-protein signaling 10 (RGS10) is an important member of the RGS family and produces biological effects in multiple organs. We used a genetic approach to study the role of RGS10 in the regulation of pathological cardiac hypertrophy and found that RGS10 can negatively influence pressure overload–induced cardiac remodeling. RGS10 expression was markedly decreased in failing human hearts and hypertrophic murine hearts. The extent of aortic banding–induced cardiac hypertrophy, dysfunction, and fibrosis in RGS10-knockout mice was exacerbated, whereas the heart of transgenic mice with cardiac-specific RGS10 overexpression exhibited an alleviated response to pressure overload. Consistently, RGS10 also inhibited an angiotensin II–induced hypertrophic response in isolated cardiomyocytes. Mechanistically, cardiac remodeling improvement elicited by RGS10 was associated with the abrogation of mitogen-activated protein kinase kinase 1/2–extracellular signal-regulated protein kinase 1/2 signaling. Furthermore, the inhibition of mitogen-activated protein kinase kinase–extracellular signal-regulated protein kinase 1/2 transduction abolished RGS10 deletion-induced hypertrophic aggravation. These findings place RGS10 and its downstream signaling mitogen-activated protein kinase kinase–extracellular signal-regulated protein kinase 1/2 as crucial regulators of pathological cardiac hypertrophy after pressure overload and identify this pathway as a potential therapeutic target to attenuate the pressure overload–driven cardiac remodeling. Abstract : Supplemental Digital Content is available in the text.